2021
DOI: 10.1016/j.rbmo.2021.06.020
|View full text |Cite
|
Sign up to set email alerts
|

Educational needs of fertility healthcare professionals using ART: a multi-country mixed-methods study

Abstract: ucational needs of fertility health care professionals using assisted reproductive technologies: A multi-country mixed-methods study,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 41 publications
(36 reference statements)
0
4
0
Order By: Relevance
“… 19 The honoraria provided following participation was adjusted based on country of practice, profession and nature of participation (interview/survey), which was approved by the ethics review board to ensure fair compensation for time and effort. Qualitative target sample sizes were calculated based on experience with similar projects, 20 , 21 and expectations towards reaching data saturation. 22 Quantitative target sample sizes were calculated so that χ 2 tests between five subgroups on a dichotomic variable would produce a statistical power of 0.8, assuming α = 0.05 and a large effect size (Cohen’s w = 0.5).…”
Section: Methodsmentioning
confidence: 99%
“… 19 The honoraria provided following participation was adjusted based on country of practice, profession and nature of participation (interview/survey), which was approved by the ethics review board to ensure fair compensation for time and effort. Qualitative target sample sizes were calculated based on experience with similar projects, 20 , 21 and expectations towards reaching data saturation. 22 Quantitative target sample sizes were calculated so that χ 2 tests between five subgroups on a dichotomic variable would produce a statistical power of 0.8, assuming α = 0.05 and a large effect size (Cohen’s w = 0.5).…”
Section: Methodsmentioning
confidence: 99%
“…A study by Sophie et al, was conducted among embryologists to assess gaps in practice. 38 % of surveyed reported sub-optimal knowledge of treatments and instruction protocols for ovarian stimulation (Péloquin et al, 2021). Qualitative and quantitative data from embryologists in the same study showed that only 86 % agreed that the optimization of embryo culture conditions is more important than assessing embryo morpho.…”
Section: Discussionmentioning
confidence: 97%
“…Afterward, clinical embryology has evolved technically, with the advancements in the field including ICSI, assisted hatching, and the availability and widespread use of preimplantation genetic testing of embryos. With the huge number of couples battling subfertility and requesting assisted reproduction comes extraordinary scientific and technological headways (Péloquin et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation